IRAN-US RELATIONS AFTER THE DEATH OF QASSEM SOLEIMANI - Firmanda Taufiq; Ayu Maulida Alkholid (Arabic Literature Department, 2021)
Iran-United States relations have up and down. Some sharp diplomatic statements made by the US president, Donald Trump, as well as the president of Iran, Ayatullah Khomeini. In fact, the sanctions that must be accepted by the US against Iran are embargo sanctions. This article aims to analyze how the future relations between Iran and the United States. Cooperation between the two countries has a history that dates back to the Cold War. Relations between these two countries based on a variety of interests, including economic, political, military, ideological, and security considerations . The theory used in this research is balance of power theory. The US has major interest in the Middle East and Iran is a rival of the US in achieving that interest. Nevertheless, many US foreign policies are caused tension between the two countries. Conversely, Iran has considerable economic importance, but the role of the Iran government elite also has a significant influence in the determination of their foreign policy. The findings in this study, despite challenges and complicated processes, the US and Iran are eternal rivals in the fusion of power and political influence in the Middle East, and relations between both will continue to fluctuate .